Daropeptide natural products - Suze Ma; Sijia Guo; Wei Ding; Qi Zhang (Exploration of Drug Science)
Cyclophane-containing peptides comprise an important group of macrocyclic peptides with unique structural properties and pharmaceutical relevance. Darobactin A is a ribosomally synthesized and post-translationally modified peptide (RiPP) antibiotic, which features an unusual biscyclophane moiety formed via the class-defining ether crosslink in addition to a carbon-carbon (C-C) crosslink. Because darobactin-like peptides (daropeptides) are widespread in nature, further exploration of these emerging RiPP natural products featuring ether crosslinked cyclophane could facilitate the discovery and development of new bioactive peptides. This perspective provides updated insights into the biosynthesis and classification of daropeptides, highlighting the potential to manipulate daropeptide maturases to access novel bioactive peptide cyclophanes.